Potensi Kuliner Tradisional Khas Keraton Surakarta, Solo, Jawa Tengah - Agustina Mellyani; Dewi Ayu Kusumaningrum (Jurnal Sains Terapan Pariwisata, 2020)
Traditional Keraton cuisine is generally based on rice and vegetables, not much use of meat as raw material. Dutch culinary has influenced the typical culinary delights of the Palace. The special culinary delights of the Keraton are still consumed by the Keraton family to this day and are displayed at ancestral offerings, religious events, ascending ceremonies, which always serve food offerings and food for members of the palace, as well as guests who come. This has the potential to develop the Keraton’s culinary delights into the culinary delights of the general public in Solo. Solo City itself has a culinary night spot called Gladag Langen Bogan (Galabo). The problem raised in this research is the culinary specialties of the Surakarta Palace which are not yet widely known. The research objective was to identify various traditional Keraton culinary delights that could become potential culinary developments in Solo. The descriptive qualitative research method with the speakers is the family of the Keraton Surakarta, the servants of the Keraton Surakarta, the head of the Keraton kitchen, tourists, the Tourism Office and the owner of the traditional food business of the Keraton Surakarta. Sources of data obtained directly from the research location through interviews, observation, and documentation. The traditional culinary specialties of Keraton Surakarta are Stupp Macaroni, Timlo Solo, Gereh Fish Vegetable, Bestik, Nasi Jemblung, Londoh Pindang Rice, Bestik Galatin, Solo Strait, Tengkleng, Gudeg, Nasi Liwet, Semar Mendem, Solo Sausage, Es Dawet Selasih, Es Puter Java, Jamu and Serabi Solo. The culinary specialties of the Surakarta Palace such as Stupp Macaroni, Gereh Fish Vegetable, Solo Sausage, Gudeg and Es Puter Jawa cannot be found or traded in the area around the Surakarta Palace. This is possible due to the lack of innovation in the preparation, presentation of culinary delights and also the lack of introduction to the typical culinary delights of the Surakarta Palace.